Cassell's encyclopaedia of world literature - Buchanan-Brown, John (Cassell, 1973)
Volume 1 contains the histories of individual literatures, definitions of literary terms, descriptions of literary genres, accounts of schools and movements, of themes that have inspired writers and of topics of general literary interest. Volumes two and three contain the biographical information including an assessment of the individual writer's contribution to literature.